1969
DOI: 10.12669/pjms.322.9510
|View full text |Cite
|
Sign up to set email alerts
|

Plastibell Device Circumcision versus Bone Cutter Technique in terms of Parent’s Satisfaction and Outcomes

Abstract: Objective:To compare the rate of complications of Plastibell and bone cutter circumcision technique and recognition of top worries and satisfaction rate in the mind of parents before and after the procedure of Plastibell device (PD) circumcision in infants less than 6 months of age.Methods:It was a descriptive prospective study conducted at department of surgery Sheikh Zayed Hospital, Rahim Yar Khan. Two hundred parents of infants of less than six months of age were recruited for this study. Infants were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…Similarly, complication rates were comparable between the 2 techniques. In the current study, the amount of blood loss and the duration of operation were less with bone-cutter circumcision compared to the plastibell device in contrast to the finding by Mehmood et al [23], who found more blood loss and longer duration of operation among infants who had bone-cutter technique compared to plastibell device. Though the duration of surgery in our study was comparable to theirs, the amount of blood in their study of 10.65±3.31mls for bone-cutter and 5.48±0.84mls for plastibell device was higher than ours.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Similarly, complication rates were comparable between the 2 techniques. In the current study, the amount of blood loss and the duration of operation were less with bone-cutter circumcision compared to the plastibell device in contrast to the finding by Mehmood et al [23], who found more blood loss and longer duration of operation among infants who had bone-cutter technique compared to plastibell device. Though the duration of surgery in our study was comparable to theirs, the amount of blood in their study of 10.65±3.31mls for bone-cutter and 5.48±0.84mls for plastibell device was higher than ours.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we recorded a complication rate of 6.7% for the plastibell device and 5.0% for the bone-cutter method which are in agreement with the above studies. Mehmood et al [23] in a similar study, reported complication rates of 3% and 1% for bone-cutter and plastibell techniques, respectively. Bawazir [30] noted more complications with plastibell compared to the Gomco clamp.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations